Konsep Bakti Pada Penyajian Gending-Gending Gambang di Desa Kwanji Sempidi - I Nyoman Mariyana (GHURNITA: Jurnal Seni Karawitan, 2021)
The concept of devotion is respect; The act of expressing loyalty, love, and submission, in Hinduism is realized through the presentation of Gambang songs that reflect the concept of devotion. As a sound instrument, the Gambang gamelan is always present and completes the Ngaben ceremony in the village of Kwanji Sempidi. Why is every cremation ritual in Kwanji village always accompanied by the Gambang gamelan? What is the meaning of the concept of devotion in the presentation of Gambang songs in Kwanji Sempidi village. The method used in this research is descriptive qualitative research method through data collection by observation, interviews, and documentation. Through this method, in the gamelan Gambang Kwanji Sempidi, the presentation of the xylophone music is a form of devotion by all the xylophones to the xylophone ancestors in Kwanji Sempidi who have educated them and at the same time proves how they protect the cultural heritage they have instilled in their generations. In playing the xylophone gending by sekaa Gambang Kwanji Sempidi, all players play the xylophone with a sense of devotion (respect and submission) to the uger gending xylophone. This respect can be seen from the coordination system between players that occurs in playing Gambang. The Gangsa instrument is the holder of the control of the song or the regulator of the way the gending is played. Other xylophone players (pengenter, pemero, stragglers, pickers) must submit to Gangsa Gambang players. Gambang Pengter has the task of regulating as well as carrying the tempo by playing the basic melodic pattern of the song. The xylophone pemo instrument, the penyelat, and the pemetit must also be able to listen to the tempo played by the xylophone Penger. Gambang Penyelat and Pemero respond to where the melody of the song is playing.